Allopolyploidy-induced rapid genomic changes in newly generated synthetic hexaploid wheat. Issue 2 (4th March 2017) - Yu, Ma; Guan, Ling-Liang; Chen, Guo-Yue; Pu, Zhi-En; Hou, Da-Bin
ABSTRACT: Although DNA elimination, gene silencing and duplication and pseudogenization are associated with allopolyploidization in wheat, the effect of allopolyploidy on the ecogeographical expansion and domestication of this species remains unknown. In the present study, we used 1862 mapped loci to investigate genetic changes associated with allopolyploidization by comparing bands between synthetic wheat SHW-L1 and its parental lines Aegilops tauschii ssp . tauschii AS60 (DD) and Triticum turgidum ssp. turgidum AS2255 (AABB). A total of 338 (18.15%) loci from AS60 or AS2255 were found to have been eliminated from SHW-L1. Of these loci, 56 were present only in AS2255; 212 ones were found only in AS60 and 70 ones were detected in both AS2255 and AS60. The different numbers of eliminated loci originating from AS2255 and AS60 suggest that the D genome of SHW-L1 suffered more disruption during the allopolyploidization process than the A and B genomes. In addition, 82 eliminated loci were tightly linked to express quantitative trait loci, with 53 of these loci containing open reading frame sequences predicted to encode proteins related to disease resistance, environmental adaption, nitrogen fixation, nitrogenase reductase and other processes. Further investigation of changes in these gene sequences should help elucidate the genetic mechanisms underlying the increased fitness, adaptability and competitiveness that have accompanied wheat during domestication.